“ISTRI KARIR MENURUT HUKUM ISLAM DAN PESPEKTIF GENDER” - Ghea Lintang Amour Vanryan; Khoirul Asfiyak; Dwi Ari Kurniawati (Jurnal Hikmatina, 2020)
AbstrackThis study aims to determine the effect of career women's attention on the success of their children's education, the strategy of career women in allocating time to pay attention to their children's education, factors that support and inhibit career women to pay attention to children's education. The main problem in this research is how is the career wife according to Islamic law and gender perspective, with sub-problems: l) how is the career wife according to the view of Islamicklaw? 2) What about a career gender perspective wife? This research is a research study (library research). The preparation of this thesis, using data collection methods in accordance with its clarification The results of the research and analysis of the author: (l) A career for a wife is based on two factors, the first is an internalo factor, which is to assist the husband in meeting the needs of the family economy.dThe two externa factors are work and career for wives who require them to leave their homes. the assessment that is owned by a woman (wife) also influences the creation of a working wife profile. The belief that a wife must make herself as much as possible, and expand her network of activities. (2) The assessment of the worlld of work they live in requires that they have to arrange time between their familly and profession. (3) Generally not found in fiqh literature which forbids wives from working, as long as there is permission from the husband and guarantees of security and safety. Scholars distinguish between a career wife who can reduce the rights of a husband or an emergency and the second is a wife who works outside the home at work that does not contain risks. The implications in this paper reinforce that permitting a woman as a wife to workbfor the public, as long as it does not make him neglect of his role in maintaining religious, customary and moralopnorms, and can fulfill the conditions and ethics of a wife who works outside the home. In addition, as a housewife must be able and master time management. Keywords: Career wife, Islamic law, Gender